The Value of Serum Cell-Free DNA Levels in Patients With Schizophrenia - Chen, Ling-yun; Qi, Jing; Xu, Hong-lei; Lin, Xiang-yun; Sun, Ya-jun; Ju, Shao-qing (Frontiers in Psychiatry, 2021)
Background: Schizophrenia is a severe mental disorder, which has a major impact on the quality of life and imposes a huge burden on the family. However, the pathogenesis of schizophrenia remains unclear and there are no specific biomarkers. Therefore, we intend to explore whether cf-DNA levels are related to the occurrence and development of schizophrenia. Methods: We analyzed and compared the concentration of cf-DNA in 174 SZ patients and 100 matched healthy controls by using quantitative real-time PCR by amplifying the Alu repeats. Results: We found that cf-DNA levels in peripheral blood reliably distinguished SZ patients from healthy controls (P < 0.05). The ROC analysis also supports the above conclusion. By tracking the absolute concentration of serum cf-DNA in primary cases, we found a distinct increase before treatment with antipsychotics, which decreased progressively after treatment. Conclusions: The present work indicates that cf-DNA may improve the efficiency of disease diagnosis, and the level of cf-DNA plays a predictive role in the development of schizophrenia. By evaluating the level of cf-DNA, we might play a certain role in a more reasonable and standardized clinical treatment of schizophrenia.